Rural Poverty and Agricultural Diversification in Thailand - Alia Ahmad; Somporn Isvilanonda (Lund University, School of Economics and Management, Department of Economics, 2003)
Thailand has experienced steady economic growth and structural changes in the economy in the last four decades that enabled her to gain a position among the newly industrialized nations. The structural changes associated with economic growth reflect the changing role of agriculture in the economy. The share of agriculture in GDP declined from 44% in early 1960s to 10% in recent years (Isvilanonda 1998). Its share in employment has shown similar trend albeit at a slower pace. The share of agriculture in employment has fallen from 83% in 1957 to 57% in 1999. The difference between the shares of agriculture in GDP and employment suggests a huge labour productivity gap between agriculture and manufacturing, and it has serious implications for rural poverty and rural/urban inequality. Although Thailand has been very successful in reducing poverty because of rapid and steady economic growth, rural poverty especially in certain regions is a serious problem. 90% of the poor live in rural areas and 2/3 of the poor live in northeastern provinces indicating high regional inequality. The productivity gap is mainly due to the inability of the manufacturing sector to absorb rural labour at a rapid rate. One of the ways of dealing with this problem is to diversify agriculture and the rural economy both at sectoral and farm-level. Thailand has been successful in sector-level diversification with regional specialization. However, this has resulted in regional disparity in agricultural development because of the inability of farmers in certain regions to diversify towards more profitable crops. This paper analyses the pattern of diversification at farm level, its effects on farm income and the constraints faced by farmers in different regions and production environments. The study is based on longitudinal household level data from two regions in Thailand - the Central Plains near Bangkok and Khon Kaen in the northeast of the country.
Keywords: O13; O18; Q18; 330; crop diversification; intensification; regional inequality